Inorganic membranes - Liu, Shaomin; Tan, X.; Li, K. (John Wiley and Sons, Inc, 2013)
This article discusses the research and development of inorganic membranes and their applications for liquid or gas separations. The general characteristics of the inorganic membranes and their historical development are introduced first followed by a brief description on the membrane morphology, preparation, and characterization. Compared to the established applications in the areas of liquid phase or particle separation, the development of inorganic membranes for gas separation is relatively new, with a more complex mechanism behind the separation and transport behavior, and therefore is the emphasis of this article. An overview of various microporous membranes including silica, zeolite, and carbon membranes and dense inorganic membranes in terms of solid oxide membranes, dual-phase membranes, and palladium-based metal membranes for gas separations, their relevant gas transport mechanisms, and future challenges are presented.